AGUNAN YANG DIAMBIL ALIH (AYDA) ATAS KREDIT MACET PADA PT. BPR TATA ANJUNG SARI - Adnyani, Luh Putu Sri; Puspawati, I Gusti Ayu; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013, 2013)
AYDA is one alternative to a takeover of problem loan taken by PT. BPR Tata Anjung Sari to decrease the number of problem loan. AYDA process has some drawbacks one of which is the presence of interested third parties who are not willing bank to taken their collateral. If this happens then the PT. BPR Tata Anjung Sari will take restructure loans. If restructuring was not successful then the bank will do the write-off of the loan. Key words : Bank, AYDA, Problem Loan, Collateral
Keywords: Bank, AYDA, Kredit Macet, Agunan